PENDIDIKAN KEINDONESIAAN DALAM PENGEMBANGAN PENDIDIKAN ISLAM BERBASIS BUDAYA LOKAL - Moh. Turmudi (Tribakti: Jurnal Pemikiran Keislaman, 2015)
Speaking of local cultural values as a cultural product of local communities, their presence at the level of the nation state is getting lost, especially when faced with the challenges of the global community. Indonesia's national culture merely as a formal object, because the object is actually a regional culture material including educational values in the area.That is why in the study of educational thought Indonesia needed an invention of tradition to create a building-type non western scientific education that seeks consciously undertake concrete activities continuing to improve, remodel, renew life system, social order or the state administration that reinforce values.Cultural studies utilizing multidisciplinary studies in cultural perspective. As it is known that the culture has a universal culture of the seven sectors, namely art, system technology, religion, social organization, knowledge systems, economic systems, and languages.